Transportation systems in buildings : CIBSE guide D: 2020. (CIBSE, 2020)
Guide D aims to provide guidance to practitioners involved in transportation systems in buildings; it will also be of interest to architects and developers, and to facilities and building managers who may not be directly concerned with the design and installation of lifts and escalators but need to understand the advice offered to them by specialists. Not least, the Guide should also be of value to students embarking on a career in mechanical, electrical or building services engineering and those already practising in these disciplines who wish to enhance their knowledge through a programme of continuing professional development. Guide D was first published in 1993 under the encouragement of Peter Day of Land Securities. It then stood beside the three CIBSE Guides - A, B and C - which CIBSE published at that time. The success of Guide D has spawned a whole raft of CIBSE Guides on various topics. Updating of Guide D has continued on a five-year cycle, with revised editions published in 2000, 2005, 2010, 2015 and now 2020, with Technical Editor.